Characterisation of phthalonitrile blends to achieve high char yield for 3D printing - Maisarah Latif (Nanyang Technological University, 2021)
The feasibility of incorporating phthalonitrile moieties, in the form of phthalonitrile (PN) blends, into acrylate photocurable resins was investigated. Various synthesized PN blends were characterised by Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) pre and post-photocuring using a UV oven. The thermal stability and structural integrity of these blends were studied based on their melting and decomposition temperatures. The solubility of these various blends was tested to identify the most soluble blend in the acrylate photocurable resins which depends on the melting temperature of the various blends. Carbonization or pyrolysis was done through TGA where the intrinsic char yield of phthalonitrile blends depends on the decomposition temperature of the various blends. The study of these various blends aims to combine carbonization and photocurable resins in Digital Light Processing photopolymerization as to 3D print functional carbon structures that can be used in advanced high-performance engineering applications. Based on the results, 2- hydroxyethyl methacrylate (HEMA) PN proved the feasibility to be possible where reasonable melting point and decomposition temperature can also be achieved. However, results are insufficient for HEMA PN to be made reliable as a high performance thermoset. Limitations include the lack of understanding of curing kinetics of PN blends. A more systematic study of curing kinetics can be explored through further characterisation by Fourier Transform Infrared (FTIR), Atomic Force Microscope (AFM), and Scanning Electron Microscope (SEM), as recommended for future works.